2013
DOI: 10.1016/j.joca.2013.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Total knee replacement; minimal clinically important differences and responders

Abstract: Due to the wide variations, MCID estimates should be calculated and used according to the baseline severity score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(109 citation statements)
references
References 32 publications
5
100
0
2
Order By: Relevance
“…Prior studies aimed at defining the MCID after TKA have demonstrated that 12% to 51% of patients do not experience this degree of improvement postoperatively with respect to pain and function [2,7,9,11]. With limited appropriateness criteria, the decision to pursue surgery is complex and multifactorial for both the patient and physician.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies aimed at defining the MCID after TKA have demonstrated that 12% to 51% of patients do not experience this degree of improvement postoperatively with respect to pain and function [2,7,9,11]. With limited appropriateness criteria, the decision to pursue surgery is complex and multifactorial for both the patient and physician.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that distribution-based methods underestimate the amount of postoperative improvement necessary to be meaningful for patients. However, an ideal means of calculating MCID with regard to TKA, or any intervention, remains to be determined [7,9,11]. The minimum clinically important difference for a specific intervention is ultimately defined by what is interpreted as important to a patient and is therefore not a fixed attribute.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After applying the method, a minimum change in scores of 30 points was deemed clinically meaningful for TKA [2]. This number was further adjusted for baseline scores to account for the potential room for improvement for each patient [1,8]. Similar work is needed to derive baseline-adjusted MCID values for the shorter form to further strengthen its clinical relevance.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…The MID (synonymous with minimal clinically important difference) has been defined for other scoring systems such as the WOMAC [13] and SF-36 [14] but has not been formally defined for the OKS. Whilst progress is being made in this area, an approximation to the MID was used.…”
Section: Statistical Analysesmentioning
confidence: 99%